1989
DOI: 10.1038/340554a0
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for postsynaptic calmodulin and protein kinase activity in long-term potentiation

Abstract: The phenomenon of long-term potentiation (LTP), a long lasting increase in the strength of synaptic transmission which is due to brief, repetitive activation of excitatory afferent fibres, is one of the most striking examples of synaptic plasticity in the mammalian brain. In the CA1 region of the hippocampus, the induction of LTP requires activation of NMDA (N-methyl-D-aspartate) receptors by synaptically released glutamate with concomitant postsynaptic membrane depolarization. This relieves the voltage-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
406
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 950 publications
(420 citation statements)
references
References 39 publications
12
406
1
Order By: Relevance
“…The authors attributed this change to a shift toward reduced cortical excitability and an enhanced inhibitory drive in the model of Rett syndrome, rather than to any intrinsic anomaly in the neurons themselves. 125 Ca þ 2 /calmodulin-dependent protein kinase II (CaMKII) is an important mediator of LTP [126][127][128][129][130] and other forms of synaptic plasticity. 131 Stimuli that induce LTP also persistently activate CaMKII, which may be critical for the molecular memory of synaptic events.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%
“…The authors attributed this change to a shift toward reduced cortical excitability and an enhanced inhibitory drive in the model of Rett syndrome, rather than to any intrinsic anomaly in the neurons themselves. 125 Ca þ 2 /calmodulin-dependent protein kinase II (CaMKII) is an important mediator of LTP [126][127][128][129][130] and other forms of synaptic plasticity. 131 Stimuli that induce LTP also persistently activate CaMKII, which may be critical for the molecular memory of synaptic events.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%
“…In particular, this kinase is widely believed to be a critical mediator of long term potentiation (LTP), a cellular mechanism that is thought to underlie learning and memory (Bliss and Collingridge, 1993). Several studies have demonstrated that CaMKII is necessary for the induction of LTP (Malinow et al, 1989;Malenka et al, 1989;Silva et al, 1992;Giese et al, 1998), and that introduction of activated CaMKII is sufficient to potentiate synaptic responses in neurons (Pettit et al, 1994;Lledo et al, 1995;McGlade-McCulloh et al, 1993). CaMKII is enriched at the postsynaptic density (PSD) (Kennedy et al, 1983;Suzuki et al, 1994;Petersen et al, 2003), a protein-dense specialization at the post-synaptic membrane that is composed primarily of scaffolding proteins, ion channels, and signal transduction enzymes (Ziff, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of studies have investigated the effects of impairing enzymes targeted by CaM (e.g., NOS, CaMKII, MAPK) on learning and memory, there are relatively few reports about the effects of direct inhibition of CaM (Malenka et al 1989;Nakazawa et al 1995;Margrie et al 1998;Limback-Stokin et al 2004). We investigated the effect of CaM inhibition on olfactory learning and memory in honeybees using three structurally different CaM antagonists, W-7, TFP, and R24571, delivered at different concentrations (Fig.…”
Section: Experiments 4: Inhibition Of Cam Impairs L-ltm Retentionmentioning
confidence: 99%